1992
DOI: 10.1002/lsm.1900120504
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic laser therapy of the watermelon stomach

Abstract: Endoscopic laser therapy has been used in the treatment of vascular lesions throughout the gastrointestinal tract. The "watermelon stomach" is a pattern of vascular ectasia in the gastric antrum that results in chronic gastrointestinal blood loss and iron deficiency anemia. We have treated 7 transfusion dependent patients with a watermelon stomach using endoscopic laser therapy. Four of these patients were treated with the argon laser and 3 with the Nd:YAG laser. Patient age and prior transfusion requirements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…However, 3 patients treated successfully with an argon laser required repeated treatments [47]. In a series of 26 GAVE patients treated with argon plasma coagulation, transfusion requirements were abolished in 77% over a 16-month median follow-up period [48].…”
Section: Therapymentioning
confidence: 99%
“…However, 3 patients treated successfully with an argon laser required repeated treatments [47]. In a series of 26 GAVE patients treated with argon plasma coagulation, transfusion requirements were abolished in 77% over a 16-month median follow-up period [48].…”
Section: Therapymentioning
confidence: 99%
“…The depth of tissue injury is dependent upon the power setting, the duration of the contact and the degree of pressure applied to the targeted area (1 mm in depth for slight pressure of 2 s) Nd:YAG Laser. The hemostatic effect has been shown to be earlier compared with APC and the long-term results are similar [35]. A thermal effect can reach 4-6 mm in depth on the targeted tissue.…”
Section: Discussionmentioning
confidence: 77%
“…Special points A majority of studies have used sucralfate prophylactically in order to reduce the risk of thermal ulcer formation. One study has indicated that the mean number of treatments needed to obliterate the vascular lesions and eliminate the need for transfusions was less for Nd:YAG laser when compared with APC (2.33 ± 0.27 vs 5.75 ± 0.89) [35]. Cost-effectiveness No data are available.…”
Section: Neodymium:yttrium-aluminum-garnet Laser Therapymentioning
confidence: 97%